Disseminated Mycobacterium avium subsp. hominissuis infection and ascites in an FIV‐positive cat. (23rd September 2020) - Paharsingh, India; Suepaul, Rod; Gyan, Lana; Hosein, Ansarah; Pargass, Indira
Abstract: A domestic shorthair cat was presented to the Veterinary Teaching Hospital at The University of the West Indies with a history of anorexia, ataxia, and lethargy. On physical examination, moderate abdominal distension and a palpable abdominal fluid wave were noted. Dark yellow, cloudy fluid was collected via abdominocentesis. Fluid analysis indicated that the effusion was a transudate containing low numbers of macrophages and occasional neutrophils. Some of the macrophages contained rod‐shaped nonstaining structures of variable length (2‐4 um). These structures were also seen extracellularly in low numbers. The morphology of the structures was suggestive of Mycobacterium. The cat's condition continued to deteriorate, and it died within a few hours of being admitted. Further diagnostic tests revealed feline immunodeficiency virus (FIV) infection with concurrent Mycobacterium avium subsp hominissuis infection. To the authors' knowledge, this is the first reported case of nontubercular mycobacterial‐related ascites in a cat.